2020
DOI: 10.3390/ijerph17041337
|View full text |Cite
|
Sign up to set email alerts
|

Is Less Sedentary Behavior, More Physical Activity, or Higher Fitness Associated with Sleep Quality? A Cross-Sectional Study in Singapore

Abstract: Objectives: To examine the independent, joint, and fully combined associations of sedentary behavior (SB), moderate-to-vigorous physical activity (MVPA), and cardiorespiratory fitness (CRF) with the odds of poor sleep quality (SQ). Methods: We performed a secondary data analysis on 757 working adults (male = 345) in Singapore, with an average age of 35.2 years. The Pittsburgh Sleep Quality Index was used to assess SQ. Objectively measured MVPA and SB were each obtained using an accelerometer. A non-exercise pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
13
1
1
Order By: Relevance
“…In this sense, a recently published original study by Mitchell et al 40 including 353 women also reported no evidence of a significant relationship between physical activity and sleep quantity and quality both measured by accelerometry. Moreover, Sloan et al 41 examined the independent, joint, and fully combined associations of objectively measured sedentary behaviour and MVPA with self-reported sleep quality in 757 healthy working adults aged 21-64 years old. They showed that sedentary behaviour and MVPA levels were not significantly associated with sleep quality, which concur with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a recently published original study by Mitchell et al 40 including 353 women also reported no evidence of a significant relationship between physical activity and sleep quantity and quality both measured by accelerometry. Moreover, Sloan et al 41 examined the independent, joint, and fully combined associations of objectively measured sedentary behaviour and MVPA with self-reported sleep quality in 757 healthy working adults aged 21-64 years old. They showed that sedentary behaviour and MVPA levels were not significantly associated with sleep quality, which concur with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the Singapore Health 2012 survey [ 6 ], there is a paucity of epidemiological studies looking at nationwide prevalence of poor sleep quality and insomnia in Asian countries. Most Singaporean reports on sleep quality focused on specific demographic groups, like working adults [ 18 , 19 ] or elderly patients [ 20 ]. An oft-cited report series commissioned by Philips to track sleep quality around the world (including Singapore) used a non-probability sampling method, which inevitably contains a margin of error that cannot be accounted for [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sleep quality is associated with a myriad of sociodemographic factors. Existing Singapore reports based on non-representative samples like the ones of specific demographic [ [18] , [19] , [20] ] do not capture the true prevalence of poor sleep in the Singapore population.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms contribute to better sleep, which eventually contributes to better and more engagement in PA [ 29 ]. However, in terms of association, the absence of an association between PA and sleep quality has been concluded by some studies when both PA and sleep quality were objectively measured [ 30 ], and also when PA was objectively measured and sleep quality was subjectively reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%